Efektivitas Program Rehabilitasi dan Rekonstruksi Pasca Bencana pada Badan Penanggulangan Bencana Daerah Kabupaten Pali - Erna, Yus; Lionardo, Andries; Wulandari, Novita (Mahesa Research Center, 2024)
This research aims to analyze the effectiveness of the Post-Disaster Rehabilitation and Reconstruction Program and Efforts to Inventory and Identify Post-Disaster Damage/Losses by the Regional Disaster Management Agency of Pali Regency. Data was collected through semi-structured interviews, participant observation, and documents and analyzed qualitatively. The research results show that the effectiveness of the post-disaster rehabilitation and reconstruction program at BPBD Pali Regency faces major challenges such as less-than-optimal program integration and inadequate coordination between the government and the community. Existing facilities, such as Pusdalops PB, are not yet fully effective, so the early warning system and data integration need to be improved. Community involvement in risk planning and mitigation is very important. Regular evaluation of guidelines and policies is necessary to ensure implementation under standards. BPBD also needs to improve the way it inventory damages, including by carrying out regular FGDs and periodic data collection, to increase the effectiveness of rehabilitation and reconstruction programs.